Protease extraction from Horse mango (Mangifera foetida lour) kernels - Ahmad, Mohammad Norazmi; Yarmo, Mohd Ambar; Ibrahim, Izyanti; Abdullah, Erna Normaya (LAP Lambert Academic Publishing, 2014)
Horse mango is one of the tropical fruits that belongs from a family Anacardiaceae (mango). However, its latex is notorious for human skin due to blistering effect, suggesting the presence of strong proteolytic activity. In general, the extraction of enzymes from plants is comparatively difficult due to the presence of indigenous polyphenoloxidases and high concentration of polyphenolic compounds which promote enzymatic browning resulting in the inactivation of the enzymes and therefore compared to animals and micro-organisms, higher plants have not received much attention for enzyme histochemistry. During recent year, several new methods have been developed and many of the existing ones have been improved. These methods have been applied to the plant enzyme to understanding the properties of the enzyme. Therefore, this book is written for the scientists who are primary interested in histochemical detection of protease in plants especially horse mango (Mangifera foetida Lour). Procedure to extract, identify and assay activity in the horse mango are also given. The procedures include recommended methods and all of them have been checked by the author themselves and published in the Bioscience, Biotechnology and Biochemistry and Malaysia Journal of Chemistry.